2008
DOI: 10.1111/j.1600-0625.2008.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Multilineage differentiation potential of human dermal skin‐derived fibroblasts

Abstract: Dermal skin-derived fibroblasts from rodent and human have been found to exhibit mesenchymal surface antigen immunophenotype and differentiation potential along the three main mesenchymal-derived tissues: bone, cartilage and fat. Human dermal skin-derived mesenchymal stem cells constitute a promising cell source in clinical applications. Therefore, we isolated fibroblastic mesenchymal stem-cell-like cells from human dermis derived from juvenile foreskins, which share a mesenchymal stem cell phenotype and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
174
2
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(200 citation statements)
references
References 52 publications
19
174
2
5
Order By: Relevance
“…It was shown that human bone marrow MSC (BM-MSC) surface markers CD9, CD29, CD44, CD73, CD90, CD105, CD166 were also expressed on human dermal fibroblasts (10). Lorenz K and colleagues (11) showed similar expression patterns for CD14(-), CD29(+), CD31(-), CD34(-), CD44(+), CD45(-), CD71(+), CD73(+), CD90(+), CD105(+), CD133(-) and CD166(+) in human adipose tissue-derived stem cells and human dermal skin-derived fibroblasts. Cappellesso-Fleury S and colleagues (4) compared the expression of 25 surface markers of human BM-MSCs and human dermal fibroblasts.…”
Section: Similarities Between Mesenchymal Stem Cells and Fibroblastsmentioning
confidence: 87%
“…It was shown that human bone marrow MSC (BM-MSC) surface markers CD9, CD29, CD44, CD73, CD90, CD105, CD166 were also expressed on human dermal fibroblasts (10). Lorenz K and colleagues (11) showed similar expression patterns for CD14(-), CD29(+), CD31(-), CD34(-), CD44(+), CD45(-), CD71(+), CD73(+), CD90(+), CD105(+), CD133(-) and CD166(+) in human adipose tissue-derived stem cells and human dermal skin-derived fibroblasts. Cappellesso-Fleury S and colleagues (4) compared the expression of 25 surface markers of human BM-MSCs and human dermal fibroblasts.…”
Section: Similarities Between Mesenchymal Stem Cells and Fibroblastsmentioning
confidence: 87%
“…[21][22][23][24][25] Comparison between fibroblasts from interfollicular skin and hair follicles prompted some investigators to suggest that the niche of skin multipotent stem cells resides in the hair follicle. 7,26,27 Indeed, two recent studies confirmed the multipotent nature of rat hair follicle cells and showed similar differentiation potential to BM-MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, DP cells meet stem cell criteria. In a number of works, including those coming from our lab, it was demonstrated that DP cells, according to their characteristics, may be atributed to mesenchymal stem cells along with those derived from bone marrow and adipose tissue [23][24][25][26]. These characteristics are widely accepted criteria for mesenchymal stem cells including ibroblastic morphology, ability to adhere and to diferentiate into osteogenic, chondrogenic, and adipogenic lineages [24,27,28].…”
Section: Dermal Papilla Cells and Their Inductive Propertiesmentioning
confidence: 99%